Preparation of copolymers of acrylic acid and 3-methacryloxypropyl-trimethoxysilane by the method of emulsion copolymerization - Рубан, Олеся Владимировна; Кисельова-Логінова, Катерина Валеріївна; Попов, Євген Вадимович (Technology audit and production reserves, 2015)
The method for preparing silicone acryl polymer by emulsion copolymerization of acrylic acid and 3-methacryloxypropyl-trimethoxysilane with a reaction initiator (ammonium persulfate) is presented in the article on the basis of experimental studies. The optimum conditions of synthesis are determined. Based on the study of the kinetics of the reaction by gravimetric copolymerization method, it was found that it is desirable to conduct the reaction for 4,5 hours at 90 oC, since after this time yield of copolymer was 53,3 %. During synthesis it is obtained silicone acryl polymer that is a viscous transparent liquid without sharp odor, soluble in organic solvents. The properties of the silicone acryl polymer are investigated and characterized: molecular mass is calculated, determined the composition of the copolymer is determined and IR spectral analysis is conducted. This polymer is suitable for use in paints and varnishes as a surface modifier.